Análise das Bases Moleculares da Resistência à Isoniazida e Rifampicina em Cepas Obtidas de Pacientes com Tuberculose no Estado de Goiás - ALVES, Sueli Lemes de ávila (2010)
Multidrug-resistant tuberculosis is a challenge worldwide. Rapid diagnosis by molecular techniques can provide a more aggressive and appropriate initial therapy. This study aimed to analyze the molecular basis of resistance to isoniazid (INH) and rifampin (R) of Mycobacterium tuberculosis strains isolated from cases of human tuberculosis in Goiás and to genetically determine the causes of the observed resistances. Of the 4.607 cultures for mycobacteria processed in the period of September of 2005 and December of 2007, 24 isolates from 16 patients resistant to at least H and/or R were analyzed. We compared the results obtained by phenotypic tests with mutations in key genes responsible for the development of resistance to these drugs, the rpoB gene for isolates resistant to R and katG gene for strains resistant to H. Seventy one percent of the isolates were resistant to H, and the mutations involved with resistance observed in the katG gene were in codon 315 (41%). The most frequent mutations observed in the rpoB gene of the R resistant isolates (71%) were in codons 456 (76.5%) and 451 (17.6%). Our findings are similar to those reported in the literature. We conclude that the percentage of agreement between genotypic and phenotypic tests was 41% for H and 94% for R considering the number of isolates and 40% and 91%, respectively considering the number of patients.